A PERSPECTIVE FROM MARKETING MIX AND SALES PERFORMANCE: THE EXISTENCE OF MODERN RETAILERS AMID TRADITIONAL RETAILERS IN SONDER - Ronaldo Patrick Rumokoy; Maryam Mangantar; Emilia Gunawan (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
The rapid grow of modern retailer in almost major cities in Indonesia has an impact on economic development and has a strong effect on community decision-making about whether to shop in modern retailers or traditional retailers. This study aimed to analyze the existence of modern retailers amid traditional retailers in the perspective of marketing mix and sales performance. Descriptive qualitative approach was used in this study. Primary data was gained from interview with 30 respondents from traditional retail owner in Sonder district. Based on the result of the study, it shows (1) The presence of modern retail in Sonder district has an impact on 43% traditional retailers and 57% retailers not impacted. (2) Marketing mix strategy affecting on increasing traditional retailer sales performance which product and price variable has an important role. Meanwhile, the others remaining marketing mix strategy variable such as promotion and place did not play significant role in increasing the traditional retailer sales performance in Sonder.